2013
DOI: 10.2174/138161213804805478
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Vaccines as an Option for Preventing Cervical Malignancies: (How) Effective and Safe?

Abstract: We carried out a systematic review of HPV vaccine pre- and post-licensure trials to assess the evidence of their effectiveness and safety. We find that HPV vaccine clinical trials design, and data interpretation of both efficacy and safety outcomes, were largely inadequate. Additionally, we note evidence of selective reporting of results from clinical trials (i.e., exclusion of vaccine efficacy figures related to study subgroups in which efficacy might be lower or even negative from peer-reviewed publications)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…so the question is not whether Gardasil ® has the potential to cause serious AEs but the frequency with which this occurs, information that is not always revealed to parents. As of 2015 serious adverse events (AE's) following Gardasil ® vaccination that have been reported in the medical literature include: premature ovarian failure [78], Guillian Barre syndrome and lupus and a host of other autoimmune related diseases [79], erythema multiform and other dermatological disorders [80], nervous system disorders such as POTS and many others [34], including death [81]. Most of these events are dismissed by pharmaceutical company experts as coincidental, occurring no more often then they might have with a placebo.…”
Section: Enter Gardasilmentioning
confidence: 99%
See 2 more Smart Citations
“…so the question is not whether Gardasil ® has the potential to cause serious AEs but the frequency with which this occurs, information that is not always revealed to parents. As of 2015 serious adverse events (AE's) following Gardasil ® vaccination that have been reported in the medical literature include: premature ovarian failure [78], Guillian Barre syndrome and lupus and a host of other autoimmune related diseases [79], erythema multiform and other dermatological disorders [80], nervous system disorders such as POTS and many others [34], including death [81]. Most of these events are dismissed by pharmaceutical company experts as coincidental, occurring no more often then they might have with a placebo.…”
Section: Enter Gardasilmentioning
confidence: 99%
“…While CIN 3 infections may be a better marker, with Pap smears and treatment it too will eventually clear. Tomljenovic notes that the use of HPV of any severity is a poor marker for cervical cancer because most infections clear within 3 years [34]. In phase 3 randomized, placebo-controlled, double-blind studies, labeled the FUTURE I and FUTURE II studies, designed and funded by Merck, Gardasil ® showed a 98% effective against HPV 16 and 18 CIN 2/3women who tested negative for HPV at the beginning of the study.…”
Section: Enter Gardasilmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results of advanced phase 3 clinical trials of this vaccine indicate its efficacy to be at least comparable to Gardasil with additional protection against five more cervical cancerinducing HPV types apart from 16 and 18 [43,44]. The additional HPV types targeted by Gardasil9 are HPV 31/33/45/52/58 [45].…”
Section: Hpv Vaccines: Rationale and Developmentmentioning
confidence: 99%
“…27,29,30 While this is borne out from natural history studies of HPV infection, 4345 >26% of young women monitored for >38 months on average during a large longitudinal study who acquired an incident infection with HPV type 16 or 18 developed biopsy-confirmed CIN 2/3 within 36 months. 34 Regression from CIN 2 and CIN 3 to lower-grade lesions is estimated to occur in 43% and 32% of cases, respectively, with approximately 5% of CIN 2 and 12% of CIN 3 progressing to invasive cervical cancer.…”
mentioning
confidence: 99%